To heal or not to heal, physician, that is the question - Kernan Thomas Manion (Qualitative Research in Medicine & Healthcare)
Physicians experience mental illness, substance abuse and burnout at comparable to considerably higher rates than the general population. However, they face great risk if they acknowledge on licensing and credentialing application queries the fact of their seeking help or that they have sought such in the past. Physicians also risk allegation of having such disorders, especially by any of three major regulatory powers which have authority over their professional licenses. These entities can mandate so-called Psychological Fitness- For-Duty Evaluations (PFFDE) by non-neutral evaluators and then compel acceptance of their findings and immediate and full compliance with their recommendations, doing so in an environment devoid of due process and with no discernible recourse for the subject physician. This article strives to highlight this previously unrecognized peril and encourage further exploration of these concerns and undertaking of collaborative measures to ensure that physicians can obtain professional help when needed without causing career jeopardy while also honoring the valid quality of care and patient safety concerns of the prevailing regulatory entities.